2012
DOI: 10.3758/s13423-012-0335-6
|View full text |Cite
|
Sign up to set email alerts
|

Dual n-back training increases the capacity of the focus of attention

Abstract: Working memory (WM) training has been reported to benefit abilities as diverse as fluid intelligence (Jaeggi et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 14 publications
10
82
3
Order By: Relevance
“…While we argue that the meta-analysis of n-back training does not support the contention that Gf improves with short-term cognitive training, this does not mean that n-back training does not lead to other forms of transfer: Training on n-back is likely to lead to improvements on other tasks that are similar in design and structure to the n-back task, as demonstrated by Lilienthal, Tamez, Shelton, Myerson, and Hale (2013) and von Bastian and Eschen (2015). However, such transfer effects are neither surprising nor of much practical interest, and neither of these studies found evidence for far transfer.…”
mentioning
confidence: 90%
“…While we argue that the meta-analysis of n-back training does not support the contention that Gf improves with short-term cognitive training, this does not mean that n-back training does not lead to other forms of transfer: Training on n-back is likely to lead to improvements on other tasks that are similar in design and structure to the n-back task, as demonstrated by Lilienthal, Tamez, Shelton, Myerson, and Hale (2013) and von Bastian and Eschen (2015). However, such transfer effects are neither surprising nor of much practical interest, and neither of these studies found evidence for far transfer.…”
mentioning
confidence: 90%
“…Yet, no significant relationship has been found between the levels of dual n-back tasks and working memory because of insufficient sample size. Maybe, if the sample size increases, the levels of dual n-back tasks will be a suitable criterion to anticipate improvement of working memory (18).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, biology controls the range of talent, while behaviour and context determine the place of skill in the higher or lower range limits (21). Thus, not only the dual n-back task, but also other training methods have limitations if training continues for a long time because the pace of change is becoming lower and lower or insignificant (18).…”
Section: Discussionmentioning
confidence: 99%
“…Kane and Engle, 2002;Lilienthal et al, 2013). In school practice, this means investigating who can benefit from training.…”
Section: Discussionmentioning
confidence: 99%
“…According to Salminen, Mártensson, Schubert and Kuhn (2016), this is caused by n-back training to increase 'white matter integrity [in the brain] in pathways that connect brain regions related to WM processes (p.245). Lilienthal, Tamez, Shelton, Myerson and Hale (2013) investigated five possible processes that underlie the effects of (dual) n-back on WM, these being: improvements in executive attention; updating; focus switching; increases in the capacity of the focus of attention and increases in the capacity of short term memory (p.135). 'Executive attention' regulates the contents of the active portion of memory (Engle, 2002, p. 19).…”
Section: Working Memory In the School Perspective: Definitions Theormentioning
confidence: 99%